New La1−xTbxMnO3 nanoparticles: fabrication via wet chemical route for enhanced structural, electrical and dielectric parameters. (24th January 2018) - Warsi, Muhammad Farooq; Tayyab, Hafiz Muhammad Waqar; Agboola, Philips Olaleye; Ahmad, Sajjad; Khan, Muhammad Azhar; Shakir, Imran
Abstract: Rare earth Tb 3+ doped LaMnO3 nanoparticles were fabricated via cheap facile wet chemical micro emulsion route. X-ray diffraction and spectral analysis by Fourier transform infrared radiation spectroscopy confirmed the formation of orthorhombic structure of La1− x Tb x MnO3 nanoparticles. The crystallite size was found in the range 10–50 nm. The lattice parameters (a)–(c) and cell volume were decreased as the La 3+ was replaced with Tb 3+ . This was attributed to the smaller ionic radius of Tb 3+ (0.92 Å) as compared to that of La 3+ (1.03 Å). Scanning electron microscopic images showed that the La1− x Tb x MnO3 grains are well structured and have no cracks. They are non-homogeneous in size with occasionally aggregation. The dielectric measurements of La1− x Tb x MnO3 nanoparticles performed in the frequency range 1 × 10 6 to 3 × 10 9 Hz showed that both Tb 3+ contents and frequency decreased the dielectric parameters. At high frequency, the dipoles could not follow the alternating field and thus resulted in decreased dielectric parameters. The Tb 3+ in LaMnO3 decreased the internal viscosity of the system that affected the dielectric parameters. DC-electrical resistivity was enhanced with the increased Tb 3+ contents. This might be due to f–d orbital coupling between rare earth and transition metal cations in La1− x Tb x MnO3 nanoparticles.